2012
DOI: 10.3109/02713683.2011.635403
|View full text |Cite
|
Sign up to set email alerts
|

Filtering Bleb Structure Associated with Long-Term Intraocular Pressure Control after Amniotic Membrane-Assisted Trabeculectomy

Abstract: Intrableb structures after trabeculectomy alone versus AMT-assisted trabeculectomy were distinct. The bleb wall reflectivity in the former and the extent of the subconjunctival fluid-filled space in the latter were factors associated with long-term IOP control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 28 publications
4
24
2
Order By: Relevance
“…Only one study has reported on intrableb structures after trabeculectomy with AMT [ 18 ]. Nakamura et al [ 18 ] compared the intrableb structure after trabeculectomy between AMT and non-AMT groups using UBM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one study has reported on intrableb structures after trabeculectomy with AMT [ 18 ]. Nakamura et al [ 18 ] compared the intrableb structure after trabeculectomy between AMT and non-AMT groups using UBM.…”
Section: Discussionmentioning
confidence: 99%
“…The fluid-filled space height was measured as the maximal vertical distance in the signal void or hyporeflective area between the bottom of the inner bleb wall and the top of the sclera along a straight line perpendicular to the tangent of the sclera ( Fig 2 ). The FFSS was graded from 0 to 2 as follows: (1) score 0, no visible fluid-filled space; (2) score 1, limited and demarcated fluid-filled space with a clear posterior margin; and (3) score 2, diffuse fluid-filled space extending posteriorly beyond the view of the image field ( Fig 3 ) [ 18 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Nakamura et al 22 also reported about AM-assisted TLE, comparing the intrableb structures of AM-TLE with those of TLE alone using an ultrasound biomicroscope. The findings of that study revealed that the intrableb structures in AM-assisted TLE contained a wide fluid-filled space with a relatively thin wall, whereas those produced during TLE alone had no or minimal fluid-filled space.…”
Section: Discussionmentioning
confidence: 99%
“… 43 However, other studies, including two random ized clinical trials, assessing primary trabeculectomy with amniotic membrane vs primary trabeculectomy alone (without the use of MMC or 5FU) for POAG have demons-t rated no sign ifica nt benefit in IOP cont rol at the 1 and 2-year time points. 44 - 46 These differences in reported out comes may partly be due to the different techniques of amniotic membrane placement as well as the use of antimeta bolites. Nevertheless, the evidence base for the use of amniotic membrane in glaucoma filtration surgery currently remains inconclusive.…”
Section: Introductionmentioning
confidence: 99%